1980
DOI: 10.1136/jcp.33.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the ultrastructure of human nasal cilia including abnormalities found in retinitis pigmentosa.

Abstract: SUMMARYThe electron microscopic structure of cilia from the inferior turbinate of the nose was studied in 12 adults, four with chronic sinusitis, one with allergic rhinitis, two with bronchiectasis, three with deviated nasal septum, and two normals. The changes are compared with those found in nasal cilia in 14 patients with retinitis pigmentosa.There were compound cilia in the seven cases with chronic sinusitis, allergic rhinitis, and bronchiectasis but, apart from this, the structure of the cilia was similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 19 publications
0
16
1
Order By: Relevance
“…It is impossible to isolate the contribution of either of these factors but it is likely that the technical problem of fixation and resolution of the tissue plays the major role. This has been noted previously in cilia from 10 "normal" subjects (22) when only 31.3% of the expected total number of dynein arms could be observed. This was considerably less than the number we recorded and could be because four of the subjects in the other study had chronic sinusitis and one had allergic rhinitis.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…It is impossible to isolate the contribution of either of these factors but it is likely that the technical problem of fixation and resolution of the tissue plays the major role. This has been noted previously in cilia from 10 "normal" subjects (22) when only 31.3% of the expected total number of dynein arms could be observed. This was considerably less than the number we recorded and could be because four of the subjects in the other study had chronic sinusitis and one had allergic rhinitis.…”
Section: Discussionmentioning
confidence: 67%
“…Fox et al (22) observed that 4% of cilia did not have the 9 + 2 microtubular arrangement and Rossman et al (15) found 1.7% of cilia with an abnormal number of doublet microtubules and 0.6% with abnormal number of central pair microtubules. We found 4.1 and 1.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormalities in cilia have been reported in X-linked and autosomal types of RP [Arden and Fox, 1979;Fox et al, 1980;Hunter et al, 1988]. The localization of RPGR to the rod and cone photoreceptor connecting cilium [Hong et al, 2000] raises the possibility that the observed ciliary abnormalities in XLRP are associated with RPGR mutations.…”
Section: Ciliary Abnormalities In Xlrpmentioning
confidence: 98%
“…Various investigators have reported abnormalities of nasal cilia in patients with bronchiectasis under electron microscope. [8][9][10] Neutrophil elastase is a serine proteinase that has been implicated in the pathogenesis of bronchiectasis, emphysema, and adult respiratory distress syndrome. It leads to mucous gland hyperplasia, increased airway secretion, damage of the ciliated epithelium, and acceleration of airway inflammation.…”
Section: Discussionmentioning
confidence: 99%